Child sexual abuse prevention: A qualitative study of teachers’ educational needs - Tetti Solehati; Cecep Eli Kosasih; Yanti Hermayanti; Henny Suzana Mediani (Belitung Nursing Journal, 2023)
Background: Child sexual abuse (CSA) has emerged as a global concern, particularly affecting children in Indonesia. However, there remains a scarcity of research on CSA within the Indonesian context. Objective: This study aimed to explore the educational needs of primary school teachers in preventing child sexual abuse. Methods: A qualitative descriptive study design was employed, with eight teachers and school principals selected through purposive sampling. Data were collected through focus group discussions and analyzed using content analysis. Results: Six categories emerged: 1) The risk of sexual abuse, 2) The necessity for clear CSA preventive regulations and sanctions for abusers, 3) Lack of CSA program socialization, 4) The need for structured CSA prevention education for children, 5) The importance of effective coordination with various relevant stakeholders, and 6) The presence of barriers and obstacles. Conclusion: This study provides valuable insights into the educational prerequisites for teachers to implement CSA prevention measures effectively. The findings emphasize the pressing need for school teachers to develop and implement CSA prevention programs, with the government’s and nursing professionals’ support, to enhance educators’ abilities in combating CSA. Nurses have a pivotal role in preventing and addressing child sexual abuse, and they should actively contribute to improving child safety and well-being through knowledge, collaboration, and advocacy for comprehensive prevention strategies.